(3GdCOH hGdeQhAIs - (3UGdM Hf LfGM GdQHYjs
(3ChdgG (B:s
(3bGd UGdM Hf LfGM(B: (3CYde Cf GdYQH bO JLYd GdTF GdhGMO CSeGA hJSej HGdTF GdhGMO pCTjGA aEf Pdc ef GdeQhAI, hEfeG GdeQA HeQhAJg, aGdeQhAI ELJfGH GdQLd eG ojTjfg s
(3BNQgG (B:s
(3hdh cfJ eKd GdfUd CdajJ bGFdkG CdG eG dgPG GdfUd djS HUGQe Je cJGH UGdM Hf LfGM s
(3HgG HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B18 s
Keywords: (3GdCOHs